1993
DOI: 10.1029/93ja00055
|View full text |Cite
|
Sign up to set email alerts
|

Spheroidal models of magnetic clouds and their comparison with spacecraft measurements

Abstract: We present here magnetic force-free solutions for spherical, oblate, and prolate clouds and show their magnetic field configurations. It is shown that spheroidal models can fit observed clouds as well as the cylindrical model. The spherical model is free of the limitation of the cylindrical model that allows only reduced increase of the magnetic field to 2 x of the boundary value following from properties of the Bessel functions. For the tested cases, the cloud diameters following from the fit are generally la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Chen, 1996;Kumar and Rust, 1996;Vandas et al, 1993), it is numerical simulations that have shed the most light on the dynamics of ICMEs. We focus here on such simulations.…”
Section: Results From Numerical Modelsmentioning
confidence: 99%
“…Chen, 1996;Kumar and Rust, 1996;Vandas et al, 1993), it is numerical simulations that have shed the most light on the dynamics of ICMEs. We focus here on such simulations.…”
Section: Results From Numerical Modelsmentioning
confidence: 99%
“…Some of these models obtained a better fit of the field intensity in a MC/flux rope than the Lepping et al (1990) model; for other recent MC/flux rope models see Sonnerup (2001, 2002); Hidalgo et al (2002); Hidalgo (2003); Li et al (2001); Mulligan et al (1999);and Vandas et al (2005a, b). The cylindrical force free flux rope model for MCs has been challenged via comparison with spheroidal models (spherical, oblate, and prolate) by Vandas et al (1993). In particular, they found that for 14 structures considered, primarily from IMP data, the spheroidal model fits were of comparable accuracy to the cylindrical model fits, but the estimated diameters were generally larger for the spheroidal models.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…15d. Spheroidal models can fit the magnetic field data as well as the flux rope models and capture many com- Marubashi and Lepping (2007), copyright by the authors; panel (d) from Vandas et al (1993), copyright by AGU plexities of the magnetic field profiles, such as sinusoidal, double peaked and plateau type profiles (e.g., Vandas et al 1993). However, as mentioned above, observations give strong support for flux ropes curving back and being attached to the Sun, and as shown before, when the expansion and elliptical cross-sections are allowed, flux rope models can also explain many of the asymmetries.…”
Section: Global Structure Of Magnetic Clouds From Modellingmentioning
confidence: 99%